Sphingosine-1-phosphate phosphohydrolase-1 regulates ER stress-induced autophagy - Lépine, S (Nature Publishing Group, 2011)
The sphingolipid metabolites ceramide and sphingosine-1-phosphate (S1P) have recently been implicated in autophagy. In this study, we report that depletion of sphingosine-1-phosphate phosphohydrolase-1 (SPP1), an endoplasmic reticulum (ER)-resident enzyme that specifically dephosphorylates S1P, induced autophagy. Although the mammalian target of rapamycin and class III phosphoinositide 3-kinase/Beclin-1 pathways were not involved and this autophagy was p53 independent, C/EBP homologous protein, BiP, and phospho-eucaryotic translation initiation factor-2α, and cleavage of procaspases 2 and 4, downstream targets of ER stress, were increased after SPP1 depletion. Autophagy was suppressed by depletion of protein kinase regulated by RNA-like ER kinase (PERK), inositol-requiring transmembrane kinase/endonuclease-1α, or activating transcription factor 6, three sensors of the unfolded protein response (UPR) to ER stress. Autophagy triggered by downregulation of SPP1 did not lead to apoptosis but rather stimulated, in a PERK dependent manner, the survival signal Akt, whose inhibition then sensitized cells to apoptosis. Although depletion of SPP1 increased intracellular levels of S1P and its secretion, activation of cell surface S1P receptors did not induce autophagy. Nevertheless, increases in intracellular pools of S1P, but not dihydro-S1P, induced autophagy and ER stress. Thus, SPP1, by regulating intracellular S1P homeostasis, can control the UPR and ER stress-induced autophagy.